Using Projects for the Acquisition of Vocabulary: A Teaching Experience - Martínez-Arbelaiz, Asunción (2013)
Adoptando una metodología por proyectos, realizamos una experiencia docente con un grupo de seis alumnos de español como segunda lengua en situación de inmersión. Seleccionamos sesenta y cuatro piezas léxicas, que el grupo dijo que eran nuevas para ellos, todas relacionadas con la historia del País Vasco. Los alumnos realizaron tareas de producción y de centrarse en la forma que incluían dicho vocabulario, las cuales se describen aquí. Los test administrados al terminar el proyecto dieron evidencia de que el léxico había sido fijado en la memoria. Siete semanas después los resultados se mantuvieron. Concluimos, por lo tanto, que el trabajo por proyectos repercute positivamente en la adquisición de nuevo léxico, no solo a corto plazo sino que el efecto es duradero. Adopting a project-based methodology, we carried out a teaching experience with a group of six students of Spanish as a second language in an immersion setting. We selected sixty-four lexical items that the students reported to be new to them, related to the history of the Basque Country. The students completed several production and focus-on-form tasks (described here), which included that vocabulary. The tests administered after finishing the project provided evidence that the lexicon had been fixed in the memory. Seven weeks later the same results were obtained. We conclude, therefore, that project-based work has a positive impact on the acquisition of new vocabulary, not only for short-term memory but also for long-term memory.